2020
DOI: 10.1111/gtc.12751
|View full text |Cite
|
Sign up to set email alerts
|

OPN4 belongs to the photosensitive system of the human skin

Abstract: The human skin has previously been described to be affected by light; however, the underlying mechanism remains unknown. OPN4 (melanopsin) expression was first identified in the skin of amphibians; however, whether it is also expressed and functioned in the human skin has not yet been identified. Here, we show that OPN4 was expressed in the human skin tissue and cultures of isolated keratinocytes, melanocytes and fibroblasts. Additionally, Ca2+ influx in vitro and ex vivo and phosphorylation of extracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In particular, the skin is an interesting peripheral organ in which opsin expression was first reported almost 20 years ago [23]. Since then, an increasing number of studies have demonstrated the presence and functionality of opsins in the skin [24][25][26][27][28][29][30][31][33][34][35][36][40][41][42]52,58]. Recently, the role of opsins in the skin and other peripheral tissues has been reviewed [59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the skin is an interesting peripheral organ in which opsin expression was first reported almost 20 years ago [23]. Since then, an increasing number of studies have demonstrated the presence and functionality of opsins in the skin [24][25][26][27][28][29][30][31][33][34][35][36][40][41][42]52,58]. Recently, the role of opsins in the skin and other peripheral tissues has been reviewed [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies were only performed almost a decade later by Oancea's lab pioneering reports [25][26][27]. To the present day, the photosensitive system of the skin has been shown to participate in murine and human: pigmentary responses [25][26][27][28][29][30][31], differentiation processes of keratinocytes [32,33], hair follicle growth [34], UVA-induced photoaging [35], cellular growth and apoptosis in response to UVA radiation [28], and UV-and blue light-induced calcium influx [25,27,36].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Pulmonary arterial diameter has also recently been shown to be light sensitive and use an Opn4- dependent mechanism. 61 In human tissue, it has been demonstrated that skin expresses Opn1sw , Opn2 , Opn3, Opn4, and Opn5 , 65 67 suggesting that extraretinal, opsin-mediated photoreception may extend to humans as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although individuals are exposed to visible light during daytime, little is known regarding the effects of visible light on our skin, except for the eye. Interestingly, photoreceptors that respond to various wavelengths of sunlight have been identified in the skin and their signaling mechanisms have been elucidated (Wicks et al 2011 ; Kim et al 2013 ; de Assis et al 2018 ; Regazzetti et al 2018 ; Kusumoto et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…OPN4 is observed in human keratinocytes, melanocytes, and fibroblasts. Blue light stimulates Ca 2+ influx and the phosphorylation of extracellular signal-regulated kinases 1/2 in an intensity-dependent manner (Kusumoto et al 2020 ) ( Figure 1 ).
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%